Polypharmacy, potentially inappropriate prescribing and medication complexity in Turkish older patients in the community pharmacy setting - OKUYAN, BETÜL; SANCAR, MESUT (TAYLOR & FRANCIS LTD, 2022)
Objective This study aimed to evaluate polypharmacy, potentially inappropriate prescribing (PIP) and medication complexity in Turkish older patients in the community pharmacy setting and to determine the factors associated with PIP. Methods This descriptive cross-sectional study was conducted in the community pharmacy setting in Istanbul. Older patients (>= 65 years old) who chronically used at least one medication and visited the community pharmacy for any reason in the past 4 months were invited in this study. PIP was determined by using the Ghent Older People's Prescriptions Community Pharmacy Screening (GheOP(3)S)-tool. The Turkish version of the Medication Regimen Complexity Index (MRCI) was used to determine medication complexity. Results Polypharmacy (defined as the concurrent use of five or more medications) was found in 69.0% of 158 patients. A total of 398 PIPs were detected and 83.5% (n = 132) of older patients had at least one PIP. The median (IQR) MRCI score was 12.5 (7.0-19.6). The factors associated with having >= 2 PIP were advanced age (>= 75 years old) (OR = 2.87, 95% CI 1.41-5.81;p< 0.05), higher number of chronic diseases (when >= 3, OR = 8.51, 95% CI 3.66-19.76;p< 0.05), receiving polypharmacy (OR = 8.92, 95% CI 4.09-19.46;p< 0.05), and higher MRCI scores (when MRCI >= 12.5, OR = 4.40, 95% CI 2.22-8.71;p< 0.05). Conclusion More than half of the Turkish older patients had polypharmacy and the rate of PIP was high. A higher number of PIP was associated with advanced age, higher number of chronic diseases, polypharmacy, and more complex medication regimens.
Keywords: Potentially inappropriate prescribing; potentially prescribing omission; polypharmacy; medication complexity; pharmacist; COST OUTCOMES; PEOPLE; VALIDATION; QUALITY; ADULTS